The Experimental Investigation of the Development Potential of Low-Permeability Reservoirs in the Daqing Oilfield. (29th May 2020) - Zhou, Yazhou; Yin, Daiyin
Abstract : It is very risky and difficult to develop low-permeability reservoirs, but reservoir development can be guided by the development potential of different low-permeability reservoirs. In this study, natural cores of the Daqing Oilfield were used as the research objects. The throat radius distributions of the different low-permeability cores were determined by the constant velocity mercury injection method, the movable fluid distribution characteristics were determined by nuclear magnetic resonance, and the nonlinear fluid flow characteristics were analyzed via fluid flow experimentation. From these data, the development potential for low-permeability reservoirs was determined. The results show that when the permeability is 1 × 10 − 3 μ m 2, the average throat radius is only approximately 0.9 μ m and throats with radii less than 0.1 μ m account for approximately 30% of the throats. The throats with an average radius less than 1 μ m, especially throats with radii less than 0.1 μ m, are the main factor restricting the fluid flow in these cores. The movable fluid is only approximately 20% of the fluid in a core, and the threshold pressure gradient reaches 0.15 MPa/m when the permeability is 1 × 10 − 3 μ m 2, indicating that it is more difficult to develop reservoirs with permeabilities less than 1 × 10 − 3 μ m 2 .